Comorbidity of depression and test anxiety among Vietnamese and Chinese undergraduates: cross-cultural insights from latent profile and network analyses - Thi Phuong Thao Quach; RenLai Zhou; RenLai Zhou; RenLai Zhou (Frontiers in Psychology)
IntroductionThe comorbidity of test anxiety and depression among Chinese students has been documented in numerous studies. However, despite the high prevalence of test anxiety in Vietnam, no studies to date have examined this issue within the Vietnamese context.MethodsThis study tested measurement invariance, assessed test information, and examined symptom interrelations among 884 Vietnamese and Chinese undergraduates. Data were collected using the Test Anxiety Inventory (TAI) and the Beck Depression Inventory-II (BDI-II), administered in either Vietnamese or Chinese. Analyses were conducted using multigroup latent profile analysis (MLPA) and network analysis.Results1. Both Chinese and Vietnamese undergraduates experienced comorbidity of test anxiety and depression, with Chinese students in high test anxiety groups showing a greater risk of depressive tendencies. 2. The core symptoms associated with the test anxiety–depression comorbidity differed between the two cultural groups. 3. While the network structures of the high-test-anxiety–high-depression groups showed some similarities across cultures, significant differences were observed in the low-to-moderate test anxiety and moderate depression groups.DiscussionThese findings underscore cultural nuances in the recognition and expression of test anxiety and depression among Vietnamese and Chinese undergraduates. The results highlight the importance of culturally sensitive approaches in cross-cultural mental health research and intervention design.